2008
DOI: 10.1016/j.neuroimage.2008.07.063
|View full text |Cite
|
Sign up to set email alerts
|

Measuring brain connectivity: Diffusion tensor imaging validates resting state temporal correlations

Abstract: Diffusion tensor imaging (DTI) and resting state temporal correlations (RSTC) are two leading techniques for investigating the connectivity of the human brain. They have been widely used to investigate the strength of anatomical and functional connections between distant brain regions in healthy subjects, and in clinical populations. Though they are both based on magnetic resonance imaging (MRI) they have not yet been compared directly. In this work both techniques were employed to create global connectivity m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
341
5
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 428 publications
(375 citation statements)
references
References 37 publications
23
341
5
4
Order By: Relevance
“…Despite obvious differences in scale and complexity between human and macaque brains and differences in data collection between the 2 species, the RSFC relationships that we observed in vivo were largely consistent with anatomical tracing studies in the monkey, although some differences were also noted, suggesting that this emerging technique does reflect aspects of underlying anatomical connectivity. While several recent comparisons of structural and functional connectivity support a relationship between these measures (40)(41)(42), multiple factors may influence patterns of RSFC (43,44), and, as we have observed, the relationship with anatomical connectivity is not a 1:1 correspondence.…”
Section: Discussioncontrasting
confidence: 59%
“…Despite obvious differences in scale and complexity between human and macaque brains and differences in data collection between the 2 species, the RSFC relationships that we observed in vivo were largely consistent with anatomical tracing studies in the monkey, although some differences were also noted, suggesting that this emerging technique does reflect aspects of underlying anatomical connectivity. While several recent comparisons of structural and functional connectivity support a relationship between these measures (40)(41)(42), multiple factors may influence patterns of RSFC (43,44), and, as we have observed, the relationship with anatomical connectivity is not a 1:1 correspondence.…”
Section: Discussioncontrasting
confidence: 59%
“…To conclude, this study has contributed two novel findings: (1) during exposure to cocaine cues, cocaine smokers showed a feed-forward effective connectivity pattern between the ROIs of the drug-cue processing network (amygdala → hippocampus → dorsal striatum → insula → medial frontal cortex, dorsolateral prefrontal cortex, anterior cingulate cortex) that was not present when the controls viewed the cocaine cues, and (2) craving ratings among cocaine smokers were positively correlated with the strength of causal influence of insula on dorsolateral prefrontal cortex. Future research will include using both fMRI and diffusion tensor imaging techniques to look for a relationship between effective and anatomical connectivity (Skudlarski et al, 2008) between the ROIs of the drug-cue processing network in cocaine users. Another future research will examine the influence of gender on the causal relationship between the ROIs of the drug-cue processing network during cocaine-cue exposure and empirically test the theoretical model as we propose in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, connectionbased subdivisions of premotor cortex (Johansen-Berg et al, 2004) have been found to correspond closely to the subdivisions identified using functional imaging of motor and linguistic tasks in the same individuals, and connection-based subdivisions of thalamus (Zhang et al, 2008) as well as inferior frontal cortex (Anwander et al, 2007) and cingulate cortices (Beckmann et al, 2009) have been found to match the canonical functional parcellations of these areas. In a less function-specific vein, other groups have investigated the relationship, across the brain, between so-called "functional connectivity" which is assessed using correlations in resting-state BOLD signal with structural connectivity identified using diffusion imaging (Greicius et al, 2009;Hagmann et al, 2008;Honey et al, 2009;Koch et al, 2002;Skudlarski et al, 2008;van den Heuvel et al, 2008van den Heuvel et al, , 2009van den Heuvel et al, 2009;Van Dijk et al, 2010). These studies are of a more exploratory nature, because the functional significance and neurophysiological basis of the correlation patterns in resting-state BOLD signal are not well understood.…”
Section: Functional Connectomicsmentioning
confidence: 99%